Fatty acid metabolites of Dendrobium nobile were positively correlated with representative endophytic fungi at altitude - Zhao, Yongxia; Qin, Lin; Tan, Daopeng; Wu, Di; Wu, Xingdong; Fan, Qingjie; Bai, Chaojun; Yang, Jiyong; Xie, Jian; He, Yuqi (Frontiers in Microbiology, 2023)
Altitude, as a comprehensive ecological factor, regulates the growth and development of plants and microbial distribution. Dendrobium nobile (D. nobile) planted in habitats at different elevations in Chishui city, also shows metabolic differences and endophytes diversity. What is the triangular relationship between altitude, endophytes, and metabolites? In this study, the diversity and species of endophytic fungi were tested by ITS sequencing and metabolic differences in plants were tested by UPLC‒ESI‒MS/MS. Elevation regulated the colonization of plant endophytic fungal species and fatty acid metabolites in D. nobile. The results indicate that and high altitude was better for the accumulation of fatty acid metabolites. Therefore, the high-altitude characteristic endophytic floras were screened, and the correlation with fatty acid metabolites of plants was built. The colonization of T. rubrigenum, P. Incertae sedis unclassified, Phoma. cf nebulosa JZG 2008 and Basidiomycota unclassified showed a significantly positive correlation with fatty acid metabolites, especially 18-carbon-chain fatty acids, such as (6Z,9Z,12Z)-octadeca-6,9,12-trienoic acid, 3,7,11,15-tetramethyl-12-oxohexadeca-2,4-dienoic acid and Octadec-9-en-12-ynoic acid. What’s more fascinating is these fatty acids are the essential substrates of plant hormones. Consequently, it was speculated that the D. nobile- colonizing endophytic fungi stimulated or upregulated the synthesis of fatty acid metabolites and even some plant hormones, thus affecting the metabolism and development of D. nobile.